An analysis of the clinical application of paliperidone palmitate injection based on real-world - Liu, Ruixue; Liu, Chunxiao; Hu, Di; Wang, Longkun; Feng, Dianwei; Guo, Tongxin; Wang, Ying (Frontiers in Pharmacology, 2025)
ObjectiveTo analyze the clinical application, adherence and relapse of paliperidone palmitate (PP) injection.MethodThe information of patients treated with PP 1-month (PP1M), patients switching from PP1M to paliperidone palmitate 3-month (PP3M), and the relapse of patients after discharge from 1 January 2021 to 31 December 2023 was retrieved from the electronic medical record system. Descriptive statistics, two-tailed t-test and Chi-Squared test are used to process data.Results189 patients were administered with PP1M in this study accounted for 0.88% of all inpatients. 5 (9.09%) patients were switched from risperidone long-acting injection (RLAI) to PP1M. 45 (∼23.81%) patients were switched into PP3M. The patients without relapses were twice than relapsed patients after discharge of 1 year. Patients with initial episodes administered with PP1M showed fewer relapses than patients with non-initial episodes (11.11% vs. 34.72%; aP < 0.05). 75 (39.68%) patients adhering to PP1M or PP3M after discharge showed fewer relapses than patients discontinuing injection (20.00% vs. 35.09%; bP >0.05). Besides, our results showed that the instability of disease and the non-adherence were the main factors contributing to relapse.ConclusionThe current utilization of PP1M and conversion from PP1M to PP3M is low. Patients with initial episodes with and adhering to PP injection were at lower risk of relapse. Thus, the patients’ adherence and the education about PP injections should be improved.